Cultural Wisdom in Fashion Design Learning: Bibliometric Meta-Analysis of Educational Trends - Aryati, Yulia; Husni, Rafikah; Oktaviani, Vina; Hadiastuti, Hadiastuti (YASIN, 2025)
The development of the fashion industry in the era of globalization demands adaptation to trends without abandoning cultural identity, making culture-based learning essential in fashion design education. This study aims to explore the integration of local cultural elements into the fashion design education curriculum and to assess its impact on learning through bibliometric analysis. The bibliometric method was conducted using Scopus data on publications related to fashion design and education, yielding 100 documents analyzed to identify publication trends, author and affiliation productivity, and the most cited articles. The findings reveal an annual publication growth rate of 14.9%, indicating rising interest in this topic. The analysis also identifies five of the most productive affiliations and authors, with major contributions from countries such as China, South Korea, and the United States. This study concludes that integrating local cultural values into fashion design education has considerable potential to be developed with the support of modern technology. The implications provide a foundation for developing a fashion design curriculum that is sustainable, adaptive, and culturally relevant amid the challenges of the global industry.